Enhancing Arabic Writing and Literacy through Ibda’ Magazine: A Culturally Relevant Medium in Islamic Boarding Schools - Lazuardi, Achmad Makki; Hanifansyah, Nur; Mahmudah, Menik; Wahyudi, Iqmal (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
In Arabic language education, writing remains one of the most underdeveloped yet essential skills, particularly for non-native learners who often excel in grammar drills but struggle to produce coherent and expressive texts. This study explores the role of Ibda’ Magazine as an authentic, student-centered platform to enhance Arabic writing skills and literacy among 60 third-year Tsanawiyah students at Pondok Pesantren Darullughah Wadda’wah. Using a qualitative descriptive design, the research draws on thematic analysis of student writings, classroom observations, and semi-structured interviews with both learners and instructors. The findings reveal significant improvement in students' vocabulary use, grammatical accuracy, narrative coherence, and stylistic expression. Additionally, learners reported increased confidence, motivation, and a deeper sense of ownership over their Arabic writing. The study affirms that culturally relevant, print-based media can serve as powerful pedagogical tools in bridging the gap between formal instruction and meaningful language practice, offering new pathways for Arabic writing development in Islamic educational settings.